High perinatal sodium chloride exposure and blood pressure response to chronic high sodium challenge in adult rats - Aminuddin, Niferiti; Abdul Razak, Tariq; Azzubaidi, Marwan Saad; Tin, Myo Han; Mohd Noor, Noriah (2014)
Background: An insult during a critical period of fetal development may result in increased risk for development of hypertension. Objective: This study aims at evaluating the effects of high maternal dietary sodium during pregnancy and lactation on their offspring’s blood pressure at 16 weeks upon 1 month of high dietary sodium challenge. Materials and methods: Normotensive female Sprague-Dawley rats were subjected to timed pregnancy. Pregnant rats were randomly divided into two groups and were fed normal-sodium diet (1.0%NaCl)(n=10) or high-sodium diet (3.0%NaCl) (n=10) during pregnancy and four weeks of lactation. The offspring were weaned at 4 weeks old, Thereafter, both groups were fed with NSD (1.0%NaCl) until 12 weeks old and then challenge with 3%NaCl diet for 4 weeks. Blood pressure was measured in the offsprings at 12 and 16 weeks old. Results: At 12 weeks old, the offspring’s systolic blood pressure (SBP) were significantly higher in HSD than NSD dams respectively (138.42mmHg±2.62 vs 127.27mmHg±2.00). Upon high-sodium challenge, at 16 weeks, the offspring’s SBP were significantly higher in HSD than NSD dams (143.04mmHg ±3.09 vs 131.45mmHg ±1.37). The offspring’s SBP of HSD dams were significantly greater at 16 weeks than at 12 weeks old respectively (143.04mmHg±3.09 vs 138.42mmHg±2.62). Similarly, the offspring SBP of NSD dams were significantly greater at 16 weeks than at 12 weeks old respectively (131.45mmHg ±1.37 vs 127.27mmHg ±2.00). No difference in the heart rate and food intake in both groups at 12 and 16 weeks. However, the body weight of the offspring HSD dams at 12 and 16 weeks are significantly different (389.73g±4.65 vs 443.77g±4.46 ). Similarly, the body weight of the offspring NSD dams at 12 and 16 weeks are also significantly different (384.79g±2.28 vs 434.55g±2.99). Conclusions: This suggests that there were no differences in offspring’s SBP response upon chronic high-sodium challenge in both HSD and NSD dams offspring. However, the offspring of HSD dams is at greater risk of developing hypertension than NSD dams.